Pseudocercospora fijiensis mycelia-based infection system enhances investigational efficacy of P. fijiensis-banana pathosystem - Kumakech, Alfred; Turyagyenda, Laban F.; Edema, Richard; Okori, Patrick (Brazilian Journal of Science, 2024)
Screening procedures for black Sigatoka have limitations. Thus, there is need for alternative screening procedure. A robust controlled-environment methodology for testing reaction of banana genotypes to Pseudocercospora fijiensis is, thus, still required. The objective of this study was, therefore, to assess the effect of P. fijiensis fragmented mycelia-based inoculum on black Sigatoka development in banana under screen house conditions with the view of developing a procedure for early assessment of resistance. Black Sigatoka severity increased significantly (P < 0.05) over time in all genotypes apart from Kayinja. Significant differences (P < 0.05) in severity were also recorded among the genotypes at 3, 4, 5 and 6 weeks after inoculation. All east African highland banana and plantain genotypes tested exhibited susceptible reaction, characterized by rapid progression of symptoms to necrotic lesions. Kayinja and M9 hybrids exhibited resistant reactions, characterized by small necrotic specks and chlorotic or brown blotches, respectively. The fragmented mycelia-based infection system classified the banana genotypes into resistant and susceptible clones, making it a reliable and efficient infection technique to assess black Sigatoka disease damage. The infection system is recommended for early screening for black Sigatoka resistance.